Acute Renal Vein Thrombosis Following COVID-19 in a Lupus Patient: A Case Report and Review of the Literature - Dimitra Petrou; Aggeliki Sardeli; Panayiotis Vlachoyiannopoulos; Ornella Moschovaki-Zeiger; Sophia Lionaki (Life, 2023)
Purpose: The association between COVID-19 and hypercoagulability is well established. This is a case of a patient with systemic lupus erythematosus (SLE) who developed unilateral renal vein thrombosis following COVID-19, the third case described in the international literature so far. Methods: Clinical, laboratory characteristics and outcomes of the patient were described in detail. Literature review was performed on MEDLINE database via Pubmed. Search items included COVID-19, renal infarction, and renal thrombosis. A total of fifty-three cases were located. Of these, only two patients had renal vein thrombosis but none of them carried a diagnosis of SLE. However, six cases have been published so far involving SLE patients in whom thromboembolic events developed following COVID-19, but none of them experienced renal vein thrombosis. Conclusion: The present case adds a new piece to the emerging puzzle of COVID-19 associated hypercoagulability, especially among patients with autoimmune diseases.